Pemetaan Kepemilikan Lahan Sawah dan Sumber Daya Manusia Berbasis Geospasial di Subak Anggabaya, Umadesa, dan Umalayu Kecamatan Denpasar Timur - MANALU, TUGMA JAYA; LANYA, INDAYATI; ADI, I GUSTI PUTU RATNA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2020)
Mapping of Land Ownership and Human Resources Based Geospatial in Subak Anggabaya, Umadesa, and Umalayu East Denpasar Subdisticts  Subak Anggabaya, Umadesa, and Umalayu have been recommended as Suistainable Food Agriculture Land areas. To support it, information database on agricultural resources potential are needed to support Government Regulation number 25 of  2012. The role of mapping and information is needed for planning and monitoring in maintaining land use in Subak Anggabaya, Umadesa, and Umalayu.  The purposes of research: Knowing, inventorying and describing the ownership of paddy fields in Subak Anggabaya, Umadesa, and Umalayu which are highly recommended for LP2B, develop a database of human resources in each polygon of land ownership,designing a human resources information system. Research methods use: (1) literature study, (2) satellite image analysis, (3) tentative mapping of land ownership, (4) field survey, (5) arraging resources information. The results of research showed: land ownership maps in three subak totaling is 258 polygons, consisting of 96 polygons in Subak Anggabaya, 62 polygons in Subak Umadesa and 100 polygons in Subak Umalayu. The farmer's human resources database consists of the farmer's name, farmer's address, farmer's age, farmer's education, large, owner's name, owner's address, and profit sharing system. Land ownership map consisting of owner farmers and sharecroppers. Subak Anggabaya: owner (28 peoples) large 11,5 ha,sharecroppers (35 peoples) large 12,22 ha; Subak Umadesa: owner (22 peoples) large 3,93 ha, sharecroppers (20 peoples) large 7,10 ha; Subak Umalayu: owner (32 peoples) large 11,80 ha, sharecroppers (33 peoples) large 13,25 ha.